A Rare Diagnosis in the Emergency Department: Renal Infarction - Gurger, Mehtap (Selcuk University, 2022)
Objective: Renal infarction (RI), which is caused by sudden cessation of renal blood flow, is a rare disease. In this study, we planned to investigate the demographic and clinical characteristics and outcomes of patients diagnosed with renal infarction in the emergency department. Material and Methods: Patients over the age of 18 who presented to the emergency department with abdominal/flank pain, nausea, and vomiting between 2010 and 2021 and were diagnosed with acute renal infarction in contrast-enhanced abdominal computed tomography were included in the study. The data of the patients were reviewed retrospectively. Demographic and clinical characteristics, as well as laboratory results of the patients, were recorded. Results: A total of 38 patients were included in the study. The mean age of the patients was 61.8±18 years and 63.2% (n=24) were male. The most common complaints of the patients were abdominal pain (84.2%), flank pain (68.4%), and nausea-vomiting (50%). More rarely, patients complained about chest pain, dyspnea, and fever. Acute renal failure developed in 4 patients (10.5%). While only three (7.9%) of the patients had no known disease, the others had comorbidities such as hypertension (31.6%), ischemic heart disease (31.6%), previous thromboembolic events (31.6%), diabetes (26.3%), cancer (23.7%), heart failure (21.1%), and atrial fibrillation (18.4%). The most common cause of RI was cardioembolic events (44.7%), followed by hypercoagulability (28.9%), renal artery damage (15.8%), and idiopathic causes (10.5%). Conclusion: Acute RI is a disease that is rarely detected in the emergency department. Because there is a lack of specific clinical findings, it is often overlooked or diagnosed late. Delay in diagnosis can significantly cause morbidity and mortality. The diagnosis of acute RI should be considered especially in patients with a high risk of thromboembolism and who present to the emergency department with complaints of unexplained abdominal or flank pain. © 2022 Selcuk University School of Medicine.
Acil Bölümünde Nadir Bir Tanı: Renal Enfarktüs
Keywords: department; emergency; infarction; renal